The determinants of firm start-up size: a comparison of Ireland and Portugal - Holger Görg; Eric Strobl; Frances P. Ruane (Trinity College, Department of Economics, 2000)
In this paper we provide empirical evidence on the determinants of firm start-up size using data for the manufacturing sector in Ireland, and compare our results with recent findings for Portuguese manufacturing industries (Mata and Machado, 1996). To allow for firm heterogeneity between firm entrants we use quantile regression techniques for our empirical estimation. We find that the determinants of start-up size differ in their importance for small and large-scale entrants. In particular, industry size and industry growth seem to affect largescale entrants only.
Keywords: L11; L60; 330; entry; firm start-up size; regression quantiles; Ireland; Unternehmensgründung; Verarbeitendes Gewerbe; Vergleich; Irland; Portugal